Upaya Nation Branding Brazil Melalui Telenovela - Hariono, Filianstya; Nathania, Christina; Aryani, Maria Indira (Global and Policy Journal of International Relations, 2020)
ABSTRACTStart from basic assumptions of soft power, the ability to influence others using their attraction, so other people can affected become voluntary or without threats and violence. Brazil uses soft power instruments through the Telenovela media as the nation's branding, Brazil's telenovela becomes one of Brazil's country icons, telenovela series scheduled in prime time prove how the public love to watch telenovelas, with optimism the film makers put a large capital to make this show seven bigger, they exporting Brazil telenovela to many countries not only in Latin America but also telenovela spread to other continents. Brazil telenovela is not just a money machine but also a political media of culture, tourism, a picture of social construction and romance in Brazil, telenovela becomes a melodrama series that takes the background story from Brazilian people lifes, Brazilian telenovela is often interpolated with Brazilian art such as capoeira, samba dance, actors accent, trend fashion in Brazil, camera settings that shows the beauty of the Brazilian city, the camera perspective make us want to travel or visit the city had make telenovelas story before, Brazilian telenovelas make us know what is Brazil by watching it, that show Brazil made national branding in international society.Keywords: telenovela, Brazil, soft power, nation brandingBerangkat dari asumsi dasar soft power sebagai kemampuan untuk mempengaruhi orang lain menggunakan daya tarik yang dimiliki, sehingga orang lain yang terpengaruh dan bersifat voluntary atau tanpa ancaman dan kekerasan. Brasil menggunakan instrumen soft power melalui media Telenovela sebagai nation brandingnegaranya, telenovela Brasil menjadi salah satu icon negara Brasil, penempatan serial telenovela pada prime time menunjukkan bagaimana masyarakat sangat menggemari telenovela, dengan optimisnya para pembuat film mereka meletakkan modal yang cukup besar untuk membuat tayangan ini lebih besar lagi, dengan mengekspor telenovela Brasil ini ke banyak negara tidak hanya di Amerika Latin saja tetapi telenovela Brasil merambat hingga benua lain tetapi telenovela Brasil bukan hanya sekedar mesin uang tetapi juga merupakan media politik kebudayaan, pariwisata, dan gambaran konstruksi sosial serta romansa percintaan masyarakat Brasil, telenovela menjadi serial melodrama yang mengambil latar belakang cerita dari kehidupan masyarakat Brasil secara tidak langsung telenovela Brasil sering disisipi kesenian Brasil seperti capoeira, samba dance, penggunaan logat para aktornya dan tren berpakaian yang digunakan, seting tempat dengan sudut pandang kamera yang memperlihatkan keindahan kota Brasil seakan menuntun kita untuk ingin bepergian mendatangi kota negara tersebut dengan melihat aspek-aspek tersebut meskipun kita belum pernah mendatangi negara Brasil kita akan dapat mengerti kehidupan budaya dan keadaan alam disana, begitulah cara Brasil menggambarkan atau membranding negaranya agar dapat dikenal oleh masyarakat internasional.Kata Kunci: telenovela, Brazil, soft power, nation branding